What it means to be 98% chimpanzee : apes, people, and their genes - Marks, Jonathan (Jonathan M.), 1955- (University of California Press, 2002)
Presenting the field of molecular anthropology - a synthesis of the holistic approach of anthropology with the reductive approach of molecular genetics - this text provides an understanding of the science of human evolution and confronts the problems of racial classification in science head on.